I'm, like, SO fat! : helping your teen make healthy choices about eating and exercise in a weight-obsessed world - Neumark-Sztainer, Dianne (Guilford Press, 2005)
Shows parents how to strike the difficult balance between bolstering self-esteem and offering constructive advice. This book provides science-based, practical ideas for instilling healthy eating and exercise habits, educating teens about nutrition and portion size, and talking about body image.